Pengaruh Pemberian Murottal Al-Qur’an dengan Kecemasan pada Pasien Penyakit Gagal Ginjal Kronis yang Menjalani Hemodialisa di Rumah Sakit PKU Muhammadiyah Surakarta - Lutvia Anisa Miftaqul Jannah; Endrat Kartiko Utomo; Puput Mulyono (TRIAGE Jurnal Ilmu Keperawatan, 2026)
Background: People suffering from chronic kidney disease (CKD) and undergoing hemodialysis often experience anxiety due to their chronic condition, lifelong therapy, and psychosocial impacts. One therapeutic intervention is reciting the Qur'an, which is a non-pharmacological method that can be used. Objective: To determine how recitation of the Qur'an affects the anxiety levels of patients undergoing hemodialysis for CKD. Methods: A pretest–posttest quasi-experimental study with a control group was conducted in April–May 2025 at the Hemodialysis Unit of PKU Muhammadiyah Hospital in Surakarta. A total of 24 participants were selected with the following inclusion criteria: age ≥18 years, undergoing hemodialysis for ≥6 months, conscious, and willing to participate in the study. The intervention group (n=12) received recitation of Surah Ar-Rahman for 30 minutes three times, while the control group underwent routine procedures. Anxiety was measured using the Hamilton Anxiety Rating Scale (HARS). Data analysis was performed using the Paired Sample t-test, Independent Sample t-test, and Shapiro-Wilk normality test. Results: The mean anxiety score of the intervention group decreased from 29.5 ± 5.63 to 19.33 ± 2.39, while that of the control group decreased from 27.7 ± 5.12 to 23.17 ± 3.08. A significant decrease occurred in both groups (intervention p=0.000; control p=0.004). The improvement in the control group may have been influenced by adaptation to the procedure, stable HD room conditions, or patient coping mechanisms. The post-intervention difference showed an additional effect of murottal (p=0.003), but this needs to be interpreted with caution. Conclusion: Al-Qur’an murottal therapy is effective in reducing anxiety in patients undergoing hemodialysis due to CKD and can be recommended as a spiritual-based non-pharmacological therapy in nursing